Case report: Successful treatment with daratumumab for pure red cell aplasia in a patient with mixed lymphoid chimerism after ABO-mismatched stem cell transplant for sickle cell disease - Dovern, E.; Biemond, B. J.; Nur, E. (Frontiers in Immunology, 2023)
Pure red cell aplasia (PRCA) is a serious complication after ABO-mismatched allogeneic hematopoietic stem cell transplantation (HSCT). Following HSCT, persistent anti-donor isohemagglutinins against donor ABO antigens are considered the immunological cause of PRCA. Patients with post-transplant PRCA are at risk for graft rejection and prolonged red blood cell transfusion dependency. No standard treatment exists. Recently however, the anti-CD38 monoclonal antibody daratumumab has been reported to be an effective treatment for post-transplant PRCA in patients with complete donor chimerism. Here, we describe the first case of PRCA in a patient with mixed lymphoid patient/donor chimerism that was successfully treated with daratumumab. This is also the first report of a transplant recipient with sickle cell disease who was treated with this relatively new approach. Fourteen months post-transplantation and twelve months after treatment with daratumumab, our patient has a normal complete blood count and the anti-donor isohemagglutinins remain undetectable despite mixed lymphoid chimerism. Mixed chimerism is a common manifestation in adult patients with sickle cell disease transplanted with non-myeloablative conditioning and a matched sibling donor. The application of non-myeloablative HSCT for patients with sickle cell disease is steadily increasing. Therefore, the incidence of PRCA in this setting might also increase. As the risk of graft rejection due to PRCA can be especially high in patients with mixed chimerism, clinicians should be aware that daratumumab can be an effective treatment in the setting of mixed chimerism.